Seismic behavior of chilean bridges with seismic protection devices - Moroni, María O.; Sarrazin, Mauricio; Venegas, Braian; Villarroel, Jorge (Revista de la Construcción. Journal of Construction, 2015)
Several bridges with seismic protection systems have been built in the last decade in Chile. Accelerometer networks have been installed in some of them. Seismic records have been obtained by these instruments for moderate and severe earthquakes. In this paper, records registered at Marga Marga Bridge, Amolanas Bridge and Metro Viaduct are analyzed, and analytical models of the structures are developed. The parameters used in the models are adjusted using actual records in order to obtain the best fit between models and measured structural responses, in particular, frequencies and maximum displacement. The validated models are then used to estimate maximum stresses in principal elements and to compare them with nominal values given by design codes.